Etiology and Pattern of Drug Induced Liver Injury in a Tertiary Care Hospital of Nepal - K.C., Anuj; Jha, S.; Thapa, S. (Nepal Medical College Journal, 2019)
Drug induced liver injury (DILI) is one of the common cause of liver toxicity. Most of the drugs used today are hepatotoxic. DILI accounts for approximately one-half of the cases of acute liver failure and mimics all forms of acute and chronic liver disease. It is the single most common adverse drug reaction leading to a halt in the development of new medication by pharmaceutical company, failure of new drug to obtain regulatory approval, and withdrawal or restriction of existing drug from the market. The aim of this study is to evaluate common causes and patterns of DILI in our setting. Twenty-seven patients were enrolled in the study. Ant tubercular drugs were most common cause of DILI, accounting for 48.2%. Other common causes of DILI were paracetamol (14.8%) and NSAID’s (11.1%). The most common pattern of liver injury seen was mixed pattern which was present in63%, followed by cholestatic and hepatocellular pattern. Hence, we should be very careful while prescribing these frequently used drugs.